Utilization of purple sweet potato synbiotic drink as a source of lactic acid bacteria exopolysaccharides for immunomodulation - Almira, Rehan; Winarsih, Sri; Manshur, Hanif Alamudin (Universitas Ahmad Dahlan, 2025)
Immunomodulators, such as exopolysaccharides (EPS), can be found in products processed through lactic acid bacteria (LAB) fermentation. Purple sweet potatoes have the potential to be used as ingredients for making synbiotic drinks because of the high content of oligosaccharides. This study aimed to determine the effectiveness of purple sweet potato synbiotic drinks in improving the immune system in vivo. The experiment was conducted on male mice (Balb-C, 12 weeks old, 25±5 g BW) which were given purple sweet potato synbiotic drink for 14 days with doses of A1, A2, and A3 (50, 100, 150 mg/kg BW) given once a day. On the 14th day, the mice were induced with S. aureus bacteria given intraperitoneally (1 mL, 108 cfu/mL). The immunomodulation-related parameters measured were phagocytic activity, the number of lymphocyte cells, and the relative spleen weight of mice. The results showed that the synbiotic drink of purple sweet potato (A1, A2, and A3) can increase phagocytic activity and lymphocyte cell count and have a significant effect on relative spleen weight (p<0.05). The higher the dose of synbiotic drink, the higher the phagocytic activity and the number of lymphocyte cells, and the smaller the relative spleen weight of the mice.